AMELIORATIVE EFFECT OF ASHWAGANDHA AGAINST SO2 TOXICITY ON SERUM IMMUNOGLOBULINS IN ALBINO RAT - PREETI KUMARI; ASHA AGARWAL; RAJNI SINGH (International Journal of Pharma and Bio Sciences, 2013)
The present study is designed to investigate the serum immunoglobulins viz. IgA, IgG and IgM after sub-acute (80ppm, 1h/d for 30 days) and sub-chronic (80ppm, 1h/d for 60 days) exposure to SO2 gas in albino rat. The rats six sets- control set (I) and (IV) exposed to ambient air for 30 and 60 days, experimental set (II) and (V) exposed to SO2 gas for 30 and 60 days and experimental set (III) and (VI)exposed to SO2 gas with pre-exposure supplementation of aqueous extract of ashwagandha root (5mg/rat/day) for 30 and 60 days. The result of the present study shows a significant decrease in IgA, IgG and IgM after 30 days exposure to SO2 gas, while a very highly significant decrease after 60 days exposure to SO2 gas. However, an increase in values of serum immunoglobulins were observed after supplementation of aqueous extract of Ashwagandha. Modulation in serum immunoglobulins after supplementation of Ashwagandha extract is due to antioxidant defense mechanism against SO2 toxicity.